PERAN BADAN KESATUAN BANGSA DAN POLITIK DALAM PELAKSANAAN SELEKSI PASKIBRAKA KABUPATEN SIDOARJO - Emilia Zahra; Ananta Prathama (Journal Publicuho, 2025)
This research examines and describes the role of the National and Political Unity Agency (Bakesbangpol) in the selection process of Sidoarjo Regency Paskibraka candidates. The research method used is descriptive qualitative research, in this study using three indicators of regulation, concepts, and individual behaviour from Soekanto's theory. The findings show that the role of the National Unity and Political Agency in the regulation to carry out the selection of Paskibraka candidates is considered quite good. The efforts of the National and Political Unity Agency and active participation with various parties have been the key to success in growing a generation of youth who are not only physically capable but also embody the values of the nation. The implementation of this selection process is supported by a computerized system that embodies good governance. Although several technical obstacles have been overcome, this needs to be a concern to continue to improve the quality of selection implementation in the future.